The study of rotavirus phylogenetic diversity, re-assortment and interspecies transmission and associated virome in Northern Irish livestock and wildlife. Issue Volume 1(2019)Issue A (8th March 2019) - Tregaskis, Paula Lagan; Mooney, Mark; Lemon, Ken
Abstract : Background: Rotavirus (RV) is a highly infectious pathogen of livestock causing diarrhoea and dehydration, and substantial economic loss. RV is an RNA virus with a segmented genome that has evolved significantly creating diverse strains. RV is believed to be endemic within livestock and the genotyping of positive isolates will allow the diversity of the rotavirus to be phylogenetically mapped for evidence of re-assortment and interspecies transmission. Rotavirus positive samples and rotavirus negative samples were examined using a metagenomics approach through next generation sequencing (NGS) to study the virome of symptomatic animals. Methods: RV in symptomatic livestock, and a small subset of wildlife and exotic animal faeces samples ( n =326), originating from Northern Ireland, were screened by RT PCR for the RV VP6 gene. NGS libraries using a de novo metagenomics approach were run on the MiSeq reagent V3 600 cycle as pairend reads. Data was quality checked by Fast QC, assembled in SPAdes, processed through NCBI blast (n) and then MEGAN to display the taxonomical content. Results: The prevalence of RV VP6 gene was n =108 (33 %). Initial Sanger sequencing results showed porcine G3, G4 and G5 and bovine P7 and P13 strains. Preliminary metagenomic results indicates re-assortment and interspecies transmission with a positive bovine sample showing RV acquired re-assortment from human and equine RV strains. Analysis shows there is a large viral community present in both RV positive and RV negative animals. The metagenomic profiling through NGS data set will give a better understanding of the symptomatic virome in livestock.